2019
DOI: 10.1002/anie.201913375
|View full text |Cite
|
Sign up to set email alerts
|

SERS Activity of Semiconductors: Crystalline and Amorphous Nanomaterials

Abstract: Surface‐enhanced Raman scattering (SERS) spectroscopy on semiconductors has attracted increasing attention due to its high spectral reproducibility and unique selectively to target molecules. Recently, endeavors have been made in fabricating novel SERS‐active semiconductor substrates and exploring new enhancement mechanisms to improve the sensitivity of semiconductor substrates. This Minireview explains the enhancement mechanism of the semiconductor SERS effect in a brief tutorial and summarize recent developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
127
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(127 citation statements)
references
References 65 publications
0
127
0
Order By: Relevance
“…Additionally, the analysis of the polarizability (Fig. 1 d) indicated that Nb 2 C and Ta 2 C MXenes can provide MeB and MV with a stronger amplification of the molecular polarization, respectively, thus resulting in the more significant SERS enhancement [ 54 , 55 ]. Above results indicate that both Nb 2 C and Ta 2 C MXenes can serve as potential candidates for SERS active substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the analysis of the polarizability (Fig. 1 d) indicated that Nb 2 C and Ta 2 C MXenes can provide MeB and MV with a stronger amplification of the molecular polarization, respectively, thus resulting in the more significant SERS enhancement [ 54 , 55 ]. Above results indicate that both Nb 2 C and Ta 2 C MXenes can serve as potential candidates for SERS active substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore,b y calculating the respective relative standard deviation (RSD) of signal intensities obtained from 100 spots on n-WO 3 (13.9 %) for the detection of MB (1.0 10 À6 M) ( Figure S9), significantly improved signal reproducibility is observed with respect to b-WO 3 which shows with much weaker and nonreproducible SERS performance.This is owing to arelatively strong and uniform interaction between analyte molecules and the atomically thin surface of n-WO 3 ,which contains rich and uniformly distributed interactive sites with respect to b-WO 3 ,t hereby improving interfacial charge-transfer and contributing to the overall SERS performance. [10,18] In addition to MB,afew other probe molecules are tested on the WO 3 substrates,yielding similar results.F or the probe molecule R6G,ahigh intensity SERS signal of the 612 cm À1 characteristic peak (Table S5 [19] )iseasily obtained on n-WO 3 at the low concentration of 5 10 À6 M, while the signal is barely detected on b-WO 3 or the Si wafer. Besides dye molecules,S ERS sensing is also achieved for an on-resonant organic molecule p-dimethylaminobenzaldehyde (PDAB).…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, by calculating the respective relative standard deviation (RSD) of signal intensities obtained from 100 spots on n‐WO 3 (13.9 %) for the detection of MB (1.0×10 −6 M) (Figure S9), significantly improved signal reproducibility is observed with respect to b‐WO 3 which shows with much weaker and non‐reproducible SERS performance. This is owing to a relatively strong and uniform interaction between analyte molecules and the atomically thin surface of n‐WO 3 , which contains rich and uniformly distributed interactive sites with respect to b‐WO 3 , thereby improving interfacial charge‐transfer and contributing to the overall SERS performance [10, 18] …”
Section: Resultsmentioning
confidence: 99%
“…The number of photoinduced electrons at defect states can be largely increased with the decreased temperature due to the low temperaturereduced phonon-assisted non-radiative recombination. This effect will signicantly promote PICT transition possibility from the semiconductor to probe molecule and increase the molecular Raman scattering cross section (s R ads ), 25,43 as exhibited in eqn (2). Thus, low temperature will play a signicant role in facilitating an efficient charge transfer process, magnifying the Raman scattering cross-section (s R ads ), and enabling remarkable SERS enhancement (I Raman ), according to eqn (3).…”
Section: Resultsmentioning
confidence: 98%